Anorectal contractility under basal conditions and during rectal infusion of saline in ulcerative colitis. Issue 6 (June 1988) - Rao, S S; Read, N W; Stobart, J A; Haynes, W G; Benjamin, S; Holdsworth, C D
Abstract : Pressure activity in the rectum and anal canal was measured with a multilumen probe in 29 patients with ulcerative colitis (12 active, 11 quiescent, six studied during both phases) and 18 normal controls under resting conditions and during rectal infusion of saline. Resting motor activity was significantly decreased in patients with active colitis compared with quiescent colitis (p less than 0.005) and normal controls (p less than 0.001). Forty per cent of active colitics showed a featureless record compared with only one patient with quiescent colitis and one normal subject. The volume of saline infused before leakage occurred, and the total volume retained were significantly lower (p less than 0.001) in patients with active and quiescent colitis compared with normal controls. Rectal infusion of saline provoked regular rectal contractions, of significantly higher (p less than 0.05) amplitude in patients with active colitis, than in quiescent colitis or controls. These rectal contractions were associated with simultaneous anal relaxations. During saline infusion, peak and pressures were lower in patients with ulcerative colitis than in normal subjects, but there were no significant differences in relaxation pressures. In normal subjects, the rectal pressures remained below the anal pressures throughout the saline infusion. Peak rectal pressures exceeded the anal relaxation pressures during the last five minutes of saline infusion in patients with ulcerative colitis and throughout the infusion in those patients who complained of incontinence. Results suggest that although the resting rectal motor activity is diminished in patients with ulcerative colitis, luminal distension causes the inflamed rectum to generate abnormally strong contractions that may threaten continence.